A comparative study between Desarda’s technique and Lichtenstein’s mesh repair for the treatment of inguinal hernia - Shubham Kumar,; Snigdha Sarkar,; Avijit Bakshi,; Madhumita Mukhopadhyay, (Asian Journal of Medical Sciences, 2025)
Background: Even after Lichtenstein method of tension free mesh repair became the gold standard, the myriad of new complications prompted surgeons to look for newer methods or revisit and modify the older ones. Just as history repeats itself, tissue repair started being considered again. Back home Desarda’s method of tissue repair was presented which used autologous tissue. This study was done to compare the gold standard with a cheaper method in the developing world. Aims and Objectives: The aim of this study was to compare the outcomes between patients undergoing Desarda’s repair and Lichtenstein Hernioplasty. Materials and Methods: Patients getting admitted for inguinal hernia surgery were divided into two groups (40 each), Desarda and Lichtenstein. The seven outcome measures analyzed were recurrence of hernia, post-operative pain, seroma formation, surgical site infection, operating time, post-operative hospital stay, and time to return to normal work. Results: In our study, there was significantly shorter operating time in the Desarda group. The post-operative pain scores were slightly higher in the Desarda group. During the follow-up period, there was one recurrence in each group. Seroma formation, surgical site infection, postoperative hospital stay, and time to return to normal work were all lower in the Desarda group but not clinically significant. Conclusion: Desarda’s method of hernia repair is as effective as the standard method even without mesh implantation. The lower cost (no mesh) and absence of mesh related complications are added benefits.